Habiter la Conciergerie. S’approprier l’environnement carcéral au xviiie siècle - Adrien Pitor (Criminocorpus)
In the 18th century, the Conciergerie was supposedly only a temporary place of residence. However, the minutes taken by the bailliage du Palais when escapes occurred reveal the strategies of the court officials, the staff and the prisoners to inhabit their environment and to grasp the material realities surrounding them. Despite the limitations of the writing context, the information inserted in these documents is an opportunity to tell micro-narratives of daily life, in which the logics of neighbourhood, inter-acquaintance, cooperation or opposition that are established at different levels of the prison can be read. Prisoners and staff manage, in a constrained context, to study, transform, divert and adapt their living space. This article aims to study the prison practices of the Ancien Régime in the light of the geographical approach and in particular the notion of inhabiting.